"Commenting on your work is a waste of time only!": An appraisal-based study of evaluative language in supervisory feedback. (March 2021) - Neupane Bastola, M.; Hu, Guangwei
Highlights: We examined attitudes in supervisory feedback on thesis drafts and oral defences. Appreciations dominated in such feedback, though judgments were also prominent. Instances of affect were infrequent and occurred only in oral feedback. Both written and oral feedback comments were predominantly negative. Disciplinary variations were found for several types of appreciation and judgement. Abstract: Research on supervisory feedback on master's theses, especially attitudinal stances conveyed in such feedback, is thin on the ground. Students' construal of their supervisors' attitudes, however, can have a profound impact on their engagement with supervisory feedback. Drawing on the appraisal framework, which characterizes attitudinal meanings in terms of affect (i.e., emotional responses), judgement (i.e., normative evaluation of human behaviors) and appreciation (i.e., aesthetically-/socially-based evaluation of objects and products), this study examined Nepalese supervisors' attitudinal stances communicated in written comments on master's thesis drafts ( n = 76) submitted by English-as-a-foreign-language students and oral feedback on proposal and thesis defences ( n = 89). Quantitative analyses revealed that while instances of appreciation dominated in the supervisors' use of evaluative language, judgements were also frequent, with affective responses trailing far behind. In both the oral feedback and written comments, significant disciplinary variations were observed for certain types of judgment and appreciation. These findings are discussed in terms of disciplinary culture and the potential impact of the attitudinal stances on students' learning. Implications are derived for the productive framing of supervisory feedback to facilitate students' feedback uptake.